Bioplastics - An alternative to reduce pollution: RSL - Picho Asto, Gabriela (2024)
The present study addresses a systematic literature review (RSL) on the current development of bioplastics as a sustainable alternative due to their degradability. The methodology consisted of an exhaustive search in the Scopus database using keywords about bioplastics, biodegradables, starch, among others. Inclusion and exclusion criteria were applied, finally obtaining 30 relevant articles published in the last 5 years (2018 - 2023). The results show that the main types of bioplastics in development are biodegradable plastics from fossil resources, compostable and bio-based. The degradability time varies between 6 months to 10 years depending on the materials, although few studies specify this information. The most used additives in the production of bioplastics are plasticizers, thickeners and emulsifiers. The most commonly used biodegradable materials and products include corn, potato, and cassava starch. Regarding the importance of the development of bioplastics, most studies highlight their contribution to the reduction of environmental pollution and waste management. In conclusion, the development of bioplastics from renewable sources is a sustainable and friendly alternative that guarantees their correct degradation.